ISOLASI DAN IDENTIFIKASI SENYAWA ANTIBAKTERI EKSTRAK N- HEKSAN DAUN JATI (Tectona grandis L.F) - Andi Armisman Edy Paturusi; Nurafianty Nurafianty; Rusli Rusli; Abdul Rahim (Jurnal Farmasi UIN Alauddin Makassar, 2014)
Research about Isolation and identification of jati leave extract have been done. The purpose of this research is to isolate and identify the antibacterial compound of jati leave. The sample was used in this research obtained from Pharmacognocy-Phytochemistry Laboratory Islamic  State  University of  Alauddin  Makassar  collection.  These  sample  have  antibacterial activity to Bacillus subtilis, Pseudomonas aeruginosa, Salmonella typhosa and Staphylococcus epidermidis when conducted by Bioautography Thin Layer Chromatography (TLC). Second fraction was isolated by Preparative Thin Layer Chromatography (PTLC) and result 2 bands. The second isolat tested by Bioautography Thin Layer Chromatography (TLC) and showing antibacterial activity to Bacillus subtilis, Pseudomonas aeruginosa and Salmonella typhosa and it was single isolat when treat by multi-eluen TLC and two dimension. The next step identify the second isolat by spot reagen and showing positif reaction steroid compound. Ultraviolet spectroscopy interpretation have maximum wavelength 242 nm and infrared spectroscopy showing -OH, -CH alifatic, -CO, -CH3, alkanes, alkenes and -C=C.